Occurrence of an aortic arch anomaly in two siblings born to a diabetic mother - Tokel, Kürşad; Yılmaz, Gonca; Gürakan, Berkan (The Turkish Journal of Pediatrics, 2000)
A patient with interruption of aortic arch type A, born to a diabetic mother, is described. The patient, a male infant, was the fourth child of a 29-year-old mother, and had a sibling with coarctation of the aorta. The mother had been treated for insulin-dependent diabetes mellitus for the previous 10 years. The infant died on the 3rd day of life after symptoms of cardiogenic shock. To our knowledge, interruption of aortic arch type A has not been previously described in infants of diabetic mothers. The relevance of the case is discussed and the literature reviewed.